Molecular and serologic diagnostic approaches; the prevalence of herpes simplex in idiopathic men infertile - Amirjannati, Nasser (Research and Clinical Center for Infertility, 2014)
Background: Human pathogens that can cause infertility may also affect sperm count and quality. Viral infections can be considered as direct and/or indirect cause of male factor infertility. Objective: Our goal was to investigate the prevalence of herpes simplex virus in the semen of infertile men attending the Avicenna Infertility Clinic, and to compare it with the herpes virus serology results. Materials and Methods: This cross sectional study was conducted during 2009-2010. Infertile men participating without any clinical signs of infection with herpes simplex virus, and no obvious cause for their infertility were included. Semen and blood samples were used for Polymerase Chain Reaction (PCR) and serologic testing for these people. Two samples were collected: one ml semen sample to verify the existence of genital herpes simplex virus in infertile men, and blood samples of 217 individuals tested for antibodies to herpes simplex virus. Data were analyzed by SPSS 16. Results: According to the PCR results of semen samples the prevalence of herpes simplex in semen was 12% and serologic test showed 3.2% prevalence within blood. Nine to 10% of IgM negative were PCR positive and only 2-3% of IgM positive were PCR positive. Between herpes serologic studies with positive controls and negative controls by using both tests, there was a significant positive relationship (r=0.718 and p<0.001). The relationship between semen PCR test results and serological survey of herpes patients with a negative control in both Pearson and Spearman tests was positive and significant (r=0.229 and p=0.001). Correlation between the PCR results of semen samples with two positive control subjects and a positive IgM test was statistically confirmed (r=0.235 and p<0.001). Conclusion: We recommend that if there is suspicion to herpes simplex as a microorganism that theoretically could impact semen parameters and cause infertility it is prudent to use PCR technique on semen sample rather than ELISA on serum.